Transgastric drains. Clinical experimentation - Praderi, Raúl; Davidenko, Nicolás; Gómez Fossati, Carlos; Mazza, Milton; Estefan, Alberto; Patiño, Vida (Cirugía del Uruguay, 1973)
Severa! procedures for transhepatic drainage are described: transgastric jejunostomy; transgastric pancreatic cystostomy; left hepatostomy and transgastric choledochostomy and finally, transgastric transhepatic intubation in seton. The advantages of these procedures are pointed out since, with the exception of the transgastric pancreatic cystostomy, we have never seen them described in surgical literature.